2015
DOI: 10.1136/jech-2015-206406
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of health behaviours and clinical factors to socioeconomic differences in frailty among older adults

Abstract: A lower education or a manual occupation was associated with higher frailty risk in older women. These associations were partly explained by lower alcohol consumption, higher sedentariness, and higher obesity and chronic disease rates in women with lower SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 39 publications
2
45
2
Order By: Relevance
“…[63,64] Evidence also indicates that socioeconomic inequalities in the absolute risk of mortality would obviously increase with age. [65,66] …”
Section: Discussionmentioning
confidence: 99%
“…[63,64] Evidence also indicates that socioeconomic inequalities in the absolute risk of mortality would obviously increase with age. [65,66] …”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic inequalities and disparities throughout a lifetime are important determinants of health, such that experiences in childhood and young adulthood, in addition to midlife and older age, all appear to contribute to frailty in older age [13]. Socioeconomic factors may, in part, be mediated by other behavioral changes such as differences in diet, leisure-time activities [14], or factors associated with chronic stress. Not surprisingly, we found that neurocognitive impairment was one of the strongest risk factors for frailty and slow gait.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that made use of a range of socioeconomic indices in relation to the frailty phenotype, 1 first developed in the Cardiovascular Health Study, also show gradients in frailty 7, 8, 9, 10. This inverse socioeconomic gradient is highly relevant to public health policy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for efficacy of such measures is incomplete. Previous studies examined risk factors measured at age 60 years or older, when intervention might be too late 8, 9, 17. This study addresses this gap in the evidence by analysing the role in frailty inequality of behavioural and biomedical risk factors and disease status at age 50 years.…”
Section: Introductionmentioning
confidence: 99%